The effects of liking bias on eyewitness identifications - Blank, Hartmut (UK Data Service, 2013)
Eyewitness identification evidence is less reliable than it could be. This project investigates one potential source of eyewitness error - a witness' spontaneous tendency to like or dislike lineup members – and explores ways to reduce this bias. The underlying idea is simple: Witnesses may be more likely to identify a lineup member they don’t like as the perpetrator, and less likely to identify line-up members they like. We call this liking bias. Four experiments - extending pilot work providing the first evidence of liking bias - seek to enhance our understanding of this phenomenon. This research aims to: Understand the basis of liking bias (eg, can liking be reduced to physical attractiveness, or does it have a broader basis?). Investigate variables that affect the strength of liking bias. Biasing effects on identification decisions increase as the quality of the underlying memory decreases. Consequently, liking bias should be stronger with poorer witnessing conditions, and with longer delays between witnessing and identification. Explore ways to reduce liking bias. This will include explicitly warning witnesses of potential liking bias effects, as well as testing the degree to which existing line-up procedures (including the VIPER procedure used in the UK) enhance/attenuate liking bias.